Social causation, social selection, and economic selection in the health outcomes of Chinese older adults and their gender disparities - Kangkang Zhang; Xinpeng Xu; Hua You (Elsevier, 2023)
Background: The economic selection hypothesis, which argues that the initial economic situation determines both subsequent health and economic conditions, has been drawn into the debate on causation-selection issues. This study aims to construct a path model with self-rated health and depression score of older adults as health outcomes to measure and compare the social causation forces of wealth accumulation, social selection forces of adulthood health, and economic selection forces of childhood economics, and to examine their gender disparities. Methods: Data was obtained from a sample of 19613 older adults aged 45 years or above from the 2014 life history survey and the 2015 routine follow-up survey of the China Health and Retirement Longitudinal Study. Structural equation modeling analysis was conducted employing the full information maximum likelihood estimation method. Results: The presence of social causation, social selection, and economic selection were all statistically supported. In self-rated health, social selection forces held the dominant position, while social causation forces were comparable to economic selection forces. In depression score, social selection still exhibited stronger forces than economic selection, but social causation had forces close to social selection and greater than economic selection. The forces of the three hypotheses in self-rated health did not significantly change with gender, but social causation exerted mightier forces than economic selection within the male group, unlike the female group. The forces of economic selection in depression score were greater in females than males and no significant differences were observed among the forces of the three hypotheses in the female group. Conclusions: Social causation, social selection, and economic selection operate simultaneously on the self-rated health and depression score of older adults. However, the force magnitudes of the three hypotheses and/or their rankings differ by health outcomes and gender.